Do olhar da espiral caleidoscópica do cuidado - Slomp Junior, Helvo (2024)
The field of health has as its central reference and “soul” the production of care, a polysemic and polyphonic concept, with a ubiquitous, involved in disputes over meanings. A distinction between care and clinic was proposed, the latter considered a socio-technical construction that may or may not be subsumed by care. The concepts of perspectivism and truth regimes were taken as theoretical references for the analysis of what can be enunciated as care in a certain time and place: a production of worlds and meanings. An intercessory kaleidoscopic spiral was engendered to analyze those meanings, finding three groups of perspectives: health care as a general equivalent of health practices and clinical interventions, health care as an integral and emancipatory clinic, and health care as a micropolitics in the intercessory encounter. They are multiple worlds that carry their own truths and dispute between themselves, sometimes mixing in compositions of senses. An ethical-aesthetic-political marker that we propose for the use of the health care concept would be the production of more life in the lived lives.